Effect-based monitoring to integrate the mixture hazards of chemicals into water safety plans. (16th November 2022) - Neale, Peta A.; Escher, Beate I.; de Baat, Milo L.; Dechesne, Magali; Deere, Daniel A.; Enault, Jérôme; Kools, Stefan A. E.; Loret, Jean-François; Smeets, Patrick W. M. H.; Leusch, Frederic D. L.
Abstract: Water safety plans (WSPs) are intended to assure safe drinking water (DW). WSPs involve assessing and managing risks associated with microbial, chemical, physical and radiological hazards from the catchment to the consumer. Currently, chemical hazards in WSPs are assessed by targeted chemical analysis, but this approach fails to account for the mixture effects of the many chemicals potentially present in water supplies and omits the possible effects of non-targeted chemicals. Consequently, effect-based monitoring (EBM) using in vitro bioassays and well plate-based in vivo assays are proposed as a complementary tool to targeted chemical analysis to support risk analysis, risk management and water quality verification within the WSP framework. EBM is frequently applied to DW and surface water and can be utilised in all defined monitoring categories within the WSP framework (including 'system assessment', 'validation', 'operational' and 'verification'). Examples of how EBM can be applied within the different WSP modules are provided, along with guidance on where to apply EBM and how frequently. Since this is a new area, guidance documents, standard operating procedures (SOPs) and decision-making frameworks are required for both bioassay operators and WSP teams to facilitate the integration of EBM into WSPs, with these resources being developed currently. HIGHLIGHTS: Effect-based monitoring (EBM) captures the mixture effects of the many chemicals present in water. EBM can be integrated into water safety plans (WSPs) to assess risks associated with chemical hazards. EBM can be applied in all monitoring categories in the WSP framework. While EBM has not been integrated into WSPs yet, uptake can be supported through the development of guidance documents, frameworks and standard operating procedures. Graphical Abstract